2003
DOI: 10.1002/cncr.11094
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal amphotericin B versus the combination of fluconazole and itraconazole as prophylaxis for invasive fungal infections during induction

Abstract: Glückliche Ehe: Die erste fusionierte TCNQ–TTF–TCNQ‐Triade wurde synthetisiert und strukturell charakterisiert. In der TTF‐Brücke und den Benzo‐TCNQ‐Einheiten wurde eine starke Krümmung beobachtet, was eine gute Packung für intermolekularen Ladungstransfer verhindert. Die Vis/NIR‐ und VT‐EPR‐Studien der gemischtvalenten Derivate der Triade deuten an, dass die Elektronen sich über die Donor‐TTF‐Brücke von einer Akzeptoreinheit zur anderen bewegen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 37 publications
1
43
0
1
Order By: Relevance
“…However, rates of breakthrough candidemia were similarly low with all treatments (145). Sequential azole-polyene therapy has been reported in studies of humans in the context of breakthrough infections while patients were receiving azole prophylaxis including fluconazole (174) or a combination of fluconazole and itraconazole (123). Neither study was designed to specifically examine the effectiveness of amphotericin B after azole exposure, but success rates of lipid formulations of amphotericin B for candidemia (174) and fevers or pneumonia of unknown origin (123) were similar to those reported for other published studies.…”
Section: (D) Other Combinationsmentioning
confidence: 99%
“…However, rates of breakthrough candidemia were similarly low with all treatments (145). Sequential azole-polyene therapy has been reported in studies of humans in the context of breakthrough infections while patients were receiving azole prophylaxis including fluconazole (174) or a combination of fluconazole and itraconazole (123). Neither study was designed to specifically examine the effectiveness of amphotericin B after azole exposure, but success rates of lipid formulations of amphotericin B for candidemia (174) and fevers or pneumonia of unknown origin (123) were similar to those reported for other published studies.…”
Section: (D) Other Combinationsmentioning
confidence: 99%
“…11 This group was chosen as the control group because of the similar study design. All patients in the control group received L-AmB 3 mg/kg 3 times weekly during induction chemotherapy and during the subsequent neutropenic period.…”
Section: Historical Control Groupmentioning
confidence: 99%
“…1 In addition, it has been shown that ABLC and L-AmB are equally effective in the treatment of suspected or documented fungal infections in patients with acute leukemia, but only L-AmB has been evaluated as a prophylactic agent in patients with AML or MDS. 11,20 It has been shown that L-AmB is effective as antifungal prophylaxis during induction chemotherapy for patients with AML and high-risk MDS, with 49% of patients completing prophylaxis and only 4% of patients developing proven fungal infections during LAmB prophylaxis. 11 The prospective historical control study reported herein compared ABLC with L-AmB as antifungal prophylaxis in patients with AML and highrisk MDS who were undergoing induction chemotherapy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Proven IFIs developed in 4% of the amphotericin lipid complex group and in 5% of the azole combination's recipients during a median of 12 days of therapy. 47 These data do not support the routine use of AmB and its lipid formulation as antifungal prophylaxis in this group of patients.…”
Section: Amphotericin Bmentioning
confidence: 82%